SIK2 Improving Mitochondrial Autophagy Restriction Induced by Cerebral Ischemia-Reperfusion in Rats - Zhang, Ran; Liu, Yun; Zhong, Wenhua; Hu, Zebo; Wu, Chao; Ma, Mengyao; Zhang, Yi; He, Xiangyun; Wang, Lin; Li, Shu; Hong, Yun (Frontiers in Pharmacology, 2022)
Previous studies have shown that Salt-induced kinase-2(SIK2) is involved in the regulation of a variety of energy-metabolism-related reactions, and SIK2 also can regulate angiogenesis after cerebral ischemia-reperfusion. However, whether SIK2 can regulate energy metabolism in cerebral ischemia-reperfusion injury is not clear. Mitochondria play an important role in energy metabolism, so whether SIK2 regulates energy metabolism through affecting mitochondrial changes is also worth exploring. In this study, rats were treated with AAV-SIK2-GFP to overexpression of SIK2 before middle cerebral artery occlusion(MCAO).We found that SIK2 overexpression reduced the neuronal damage and the infarct size; increased the ATP level , and increased the levels of SIK2、mammalian target of rapamycin-1 (mTORC1)、hypoxia-inducible factor-1α (HIF-1α)、 phosphatase and tensin homologue-induced putative kinase 1 (PINK1) and E3 ubiquitinligating enzyme (Parkin). Transmission electron microscopy showed that SIK2 overexpression enhanced mitochondrial autophagy. In conclusion, SIK2 can ameliorate neuronal injury and promote the energy metabolism by regulate the mTOR pathway during cerebral ischemia-reperfusion, and this process is related to mitochondrial autophagy.